Characterization and Optimization of a Conical Corona Reactor for Seed Treatment of Rapeseed - Nishime, Thalita M. C.; Werner, Jasmin; Wannicke, Nicola; Mui, Taiana S. M. [UNESP]; Kostov, Konstantin G. [UNESP]; Weltmann, Klaus-Dieter; Brust, Henrike (MDPI, 2022)
Plasma agriculture is a growing field that combines interdisciplinary areas with the aim of researching alternative solutions for increasing food production. In this field, plasma sources are used for the treatment of different agricultural goods in pre-and post-harvest. With the big variety of possible treatment targets, studied reactors must be carefully investigated and characterized for specific goals. Therefore, in the present study, a cone-shaped corona reactor working with argon was adapted for the treatment of small seeds, and its basic properties were investigated. The treatment of rapeseed using different voltage duty cycles led to an increase in surface wettability, possibly contributing to the accelerated germination (27% for 90% duty cycle). The discharge produced by the conical reactor was able to provide an environment abundant with reactive oxygen species that makes the process suitable for seeds treatment. However, operating in direct treatment configuration, large numbers of seeds placed in the reactor start impairing the discharge homogeneity.
Keywords: corona discharge; germination acceleration; non-thermal plasma (NTP); plasma agriculture; plasma source; rape-seed; seed